Agriculture's Contribution to Climate Change and Role in Mitigation Is Distinct From Predominantly Fossil CO2-Emitting Sectors - Lynch, John; Cain, Michelle; Frame, David; Pierrehumbert, Raymond (Frontiers in Sustainable Food Systems, 2021)
Agriculture is a significant contributor to anthropogenic global warming, and reducing agricultural emissions – largely methane and nitrous oxide – could play a significant role in climate change mitigation. However, there are important differences between carbon dioxide (CO2) which is a stock pollutant, and methane (CH4) which is predominantly a flow pollutant. These dynamics mean that conventional reporting of aggregated CO2-equivalent emission rates is highly ambiguous, and does not straightforwardly reflect historical or anticipated contributions to global temperature change. As a result, the roles and responsibilities of different sectors emitting different gases are similarly obscured by the common means of communicating emission reduction scenarios using CO2-equivalence. We argue for a shift in how we report agricultural greenhouse gas emissions and think about their mitigation to better reflect the distinct roles of different greenhouse gases. Policy-makers, stakeholders and society at large should also be reminded that the role of agriculture in climate mitigation is a much broader topic than climate science alone can inform, including considerations of economic and technical feasibility, preferences for food supply and land-use, and notions of fairness and justice. A more nuanced perspective on the impacts of different emissions could aid these conversations.